2022
DOI: 10.47278/journal.ijvs/2022.175
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: Alternative to Antibiotics in Poultry Production

Abstract: Poultry production is facing severe losses due to the development of resistance against most of the available antimicrobials in treating various diseases. Moreover, social stigma against the use of antibiotics is also there. As, the welfare of animals, the environment, food safety and hygiene are also important factors. Something is needed that would meet all these stigmas and still be able to provide the best growth, immunity against diseases, peak production, disease treatment and reduce economic pressure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Probiotics can reduce Salmonella infection in broiler chickens, so that chickens are healthier and nutrient absorption can be optimal (Chen et al 2012;Yu et al 2012;Wang et al 2018). Chang et al (2019) and Rashid et al (2023) reported that feed supplementation with multi-strain probiotics enhances the gut microbiota and induces distinct cytokine expression patterns in Salmonella infection. According to Kogut and Arsenault (2015), Salmonella infection can reduce production performance and cause dysbacteriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics can reduce Salmonella infection in broiler chickens, so that chickens are healthier and nutrient absorption can be optimal (Chen et al 2012;Yu et al 2012;Wang et al 2018). Chang et al (2019) and Rashid et al (2023) reported that feed supplementation with multi-strain probiotics enhances the gut microbiota and induces distinct cytokine expression patterns in Salmonella infection. According to Kogut and Arsenault (2015), Salmonella infection can reduce production performance and cause dysbacteriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic as a feed additive has proven effective in promoting the development of a beneficial microflora (Rashid et al. 2022 ), a critical factor in maintaining intestinal health , reducing the colonization of pathogenic microbes. Consequently, this improvement in chicken productivity has been linked to enhanced broiler performance (Landy and Kavyani 2013 ; Nusairat et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a significant improvement in antibody responses in broilers and layers due to MOS supplementation was also reported by other authors ( 24 , 25 ). The positive impact of prebiotics over probiotic is still under scientific debate, and there are reports that probiotic alone is adequate ( 26 ). The present investigation aimed to evaluate the advantages of administering a probiotic supplement with S. cerevisiae or L. acidophilus and/or MOS prebiotic in terms of growth performance, digestibility, carcass traits, meat quality, and blood biochemistry for broiler chickens compared to those of zinc bacitracin.…”
Section: Introductionmentioning
confidence: 99%